Application of supercritical extraction to production of low-calorie hazelnut - Pala, M; Unal, M (INTERNATIONAL SOCIETY HORTICULTURAL SCIENCE, 1997)
In this study, the chemical composition of the hazelnut samples before and after the supercritical extraction process were assessed and compared. Effects of different pressures, temperatures and extraction time on the reduction of oil content were also investigated. The experimental trials for the extraction of the hazelnuts were conducted at 200 and 280 bars and 40 degrees C and 45 degrees C for periods of 4, 6 and 12 hours. The results showed that pressure, temperature and extraction time were important factors influencing the amount of oil extraction.
Keywords: Agriculture; Plant Sciences